Handling Goal Utility Dependencies in a Satisfiability Framework - Russell, Richard; Holden, Sean (Proceedings of the International Conference on Automated Planning and Scheduling, 2010)
Goal utility dependencies arise when the utility of achieving a goal depends on the other goals that are achieved with it. This complicates the planning procedure because achieving a new goal can potentially alter the utilities of all the other goals currently achieved. In this paper, we present an encoding procedure that enables general-purpose Max-SAT solvers to be used to solve planning problems with goal utility dependencies. We compare this approach to one using integer programming via an empirical evaluation using benchmark problems from past international planning competitions. Our results indicate that this approach is competitive and sometimes more successful than an integer programming one – solving two to three times more subproblems in some domains, while being outperformed by only a significantly smaller margin in others.